2014
DOI: 10.1149/2.0071407eel
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Anodic Nanoporous Alumina via Acetylenedicarboxylic Acid Anodizing

Abstract: The nano-morphologies of anodic porous alumina formed via anodizing in a new electrolyte, acetylenedicarboxylic acid (ADCA), are described. Anodic oxides grew uniformly on the aluminum at voltage of 87.5-95.0 V, but a burned black oxide film was formed at higher voltage. The burning voltage and the current density under steady-state oxide growth decreased with solution temperature. An anodic porous alumina film with a cell size of 250 nm and nanopores measuring 100 nm could be successfully obtained by ADCA ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 30 publications
3
21
0
1
Order By: Relevance
“…However, malonic and tartaric acids have seldom been used for nanostructure fabrication because they do not perform as well with regards to self-ordering as the three major electrolytes. Chromic (H 2 CrO 4 ) [41][42][43], formic (HCOOH) [44], malic (HOOC-CH(OH)-CH 2 -COOH) [27,45,46], citric (HOOC-CH 2 -C(OH)(COOH)-CH 2 -COOH) [27,47,48], glycolic (CH 2 OH-COOH) [27], squaric (3,4-dihydroxy-3-cyclobutene-1,2-dione) [49], tartronic (HOOC-CH(OH)-COOH) [50], and acetylenedicarboxylic (HOOC-C≡C-COOH) [51] acids have also been reported as electrolytes used to fabricate porous alumina that has characteristic nanostructure morphologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, malonic and tartaric acids have seldom been used for nanostructure fabrication because they do not perform as well with regards to self-ordering as the three major electrolytes. Chromic (H 2 CrO 4 ) [41][42][43], formic (HCOOH) [44], malic (HOOC-CH(OH)-CH 2 -COOH) [27,45,46], citric (HOOC-CH 2 -C(OH)(COOH)-CH 2 -COOH) [27,47,48], glycolic (CH 2 OH-COOH) [27], squaric (3,4-dihydroxy-3-cyclobutene-1,2-dione) [49], tartronic (HOOC-CH(OH)-COOH) [50], and acetylenedicarboxylic (HOOC-C≡C-COOH) [51] acids have also been reported as electrolytes used to fabricate porous alumina that has characteristic nanostructure morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Anodic porous alumina is typically fabricated on an aluminum substrate using electrochemical anodizing (or anodization) [22][23][24][25][26]. In several acidic electrolyte solutions, the porous alumina fabricated by anodizing is self-ordered when prepared at the appropriate electrochemical conditions, including appropriate concentrations, temperatures, and voltages (or electrochemical potentials) [27][28][29][30] [50], and acetylenedicarboxylic (HOOC-C≡C-COOH) [51] acids have also been reported as electrolytes used to fabricate porous alumina that has characteristic nanostructure morphologies.In addition to these acidic electrolytes, alkaline and neutral solutions used for porous alumina fabrication were reported by several research groups. Takahashi et al reported that a porous anodic oxide film could be formed by anodizing in an H 3 BO 3 /Na 2 B 4 O 7 neutral borate solution at a high temperature [52].…”
mentioning
confidence: 99%
“…Additional dicarboxylic acids with a large molecular structure, malonic and tartaric acids, for the fabrication of anodic porous alumina were reported by Ono et al, and self-ordering was achieved by anodizing with these acids for 300 and 500 nm intervals, respectively. 22 Recently, we reported several novel electrolytes for the formation of anodic porous alumina: selenic, 23,24 acetylenedicarboxylic, 25 squaric, 26 croconic, 27 rhodizonic, 27 ketoglutaric, 28 acetonedicarboxylic, 28 and etidronic acids. 29,30 Particularly, etidronic acid anodizing exhibited large-scale self-ordering behavior measuring 530-670 nm in cell diameter.…”
mentioning
confidence: 99%
“…Cyclic oxocarbonic acids such as squaric [24], croconic, and rhodizonic [25] acid were very recently determined to be suitable organic electrolytes for fabricating porous alumina, although the details of the growth behavior are still unknown. Carboxylic acids can also be employed as suitable electrolytes for fabricating porous alumina, including oxalic [26,27], malonic [28,29], citric [30,31], malic [32], acetylenedicarboxylic [33], tartaric [34,35], tartronic [36], glycolic [37], and formic [38] acid. Because the nanostructural features and chemical properties of anodic porous alumina are determined and limited by the electrolyte used [39], the discovery of a new suitable electrolyte would expand the applicability of porous alumina.…”
Section: Introductionmentioning
confidence: 99%